Analysis of the Springate Method in Predicting Financial Distress in Banking Companies Listed on the Indonesia Stock Exchange for the 2020-2022 Period - Nurul Mifta Khairiyah; Wahyuni, Wahyuni; Indriana, Indriana (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to analyze the Springate method in predicting financial distress in banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The research method used in this research is the Springate model using the Springate financial ratio calculation method, data is processed using Microsoft Excel computer tools. The type of data used in this research is quantitative analysis. The population used in this research was 45 companies. This sample was taken from the Indonesian Stock Exchange (BEI) which was determined using a purposive sampling technique, totaling 26 companies. In this research , the data source used is secondary data in the form of banking company annual financial report data for the 2020-2022 period. The results of S-Score analysis research carried out on banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period show that 24 banking companies are in a position experiencing financial distress due to a value of less than 0,862 (S < 0,862), and 2 other companies is in the predicted healthy category because the value is more than 0.862 (S > 0,862). This means that the company is experiencing serious financial difficulties, which could lead to bankruptcy if this situation is not resolved immediately. In the context of financial distress analysis, an S-Score value of less than 0,862 indicates that a company is illiquid and unable to fulfill its financial obligations appropriately.